2002
DOI: 10.1080/1740898020070202
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Leadership ‐ The Last Male Domain?

Abstract: A previous paper (Sharp, 2001) presented evidence to suggest that men and women working in outdoor education tend to adopt different styles of leadership. It was reasoned that if this is true, then courses designed to train leaders in outdoor activities should reflect these differences if they are to be properly effective. The present study examined this hypothesis through a postal survey to over 800 people involving course providers, leaders and aspirant leaders in mountain, paddle and snow sports. There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Triumphing women's successes and raising awareness of women's contributions in society and the outdoors has also accelerated the drive toward gender equality. Typical strategies to encourage the number of women outdoor leaders from this perspective have included raising women's visibility through successful role models, challenging stereotypes about women's lack of physical or technical competence, and enhancing women's opportunities to acquire the necessary skills (Saunders & Sharp, 2002;Warren & Loeffler, 2006).…”
Section: Liberal Feminismmentioning
confidence: 99%
See 2 more Smart Citations
“…Triumphing women's successes and raising awareness of women's contributions in society and the outdoors has also accelerated the drive toward gender equality. Typical strategies to encourage the number of women outdoor leaders from this perspective have included raising women's visibility through successful role models, challenging stereotypes about women's lack of physical or technical competence, and enhancing women's opportunities to acquire the necessary skills (Saunders & Sharp, 2002;Warren & Loeffler, 2006).…”
Section: Liberal Feminismmentioning
confidence: 99%
“…Survey responses from a sample of 258 male and female instructors indicated a strong preference for maintaining the existing content of courses. However, there was some support for the provision of womenonly courses in the early stages of skill development and leadership training, to develop confidence (Saunders & Sharp, 2002). Other studies have also demonstrated the potential value of women-only training courses to develop technical skills and build confidence in a supportive atmosphere (Hornibrook, Brinkert, Parry, Seimens, Mitten, & Priest, 1997;McDermott, 2004;Warren, 1996).…”
Section: Radical Feminismmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergent analysis of women in outdoor recreation leadership has opened up questions about women in sport, women in the outdoors, and women in high-risk or adventure challenge programs (see Johnson, 1990; Jordan, 1991; Garvey and Gass, 1999; Clemmensen, 2002; Saunders and Sharp, 2002; Sharpe, 2005; Warren, 2006; Rilling and Jordan, 2007). These studies find that attitudinal gender discrepancies toward leaders also exist in the field of outdoor recreation.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that interpersonal relationships and connectedness with others were among the top benefits and motivations for working at summer camps McCole, Jacobs, Lindley, and McAvoy (2012). also reported the importance of social network between employees in the outdoor recreation environment.Gender Differences in Outdoor RecreationSaunders and Sharp (2002) assessed leadership styles between male and female outdoor leaders and found that regardless of gender, situational leaders were the most desirable individuals in the outdoor recreation field. Respondents believed the most effective leader had a mix of masculine and feminine leadership attributes, exemplifying a flexible leadership style.…”
mentioning
confidence: 99%